A more accurate method to interpret lactate dehydrogenase (LDH) isoenzymes' results in patients with uterine masses. (May 2019) - Di Cello, Annalisa; Borelli, Massimo; Marra, Maria Luisa; Franzon, Marco; D'Alessandro, Pietro; Di Carlo, Costantino; Venturella, Roberta; Zullo, Fulvio
Abstract: Objective: Since there are no approved reliable biomarkers for detecting preoperatively uterine sarcoma, lactate dehydrogenase (LDH) isoenzymes are usually required. We first evaluated the role of LDH isoenzymes in detecting uterine sarcoma risk, and then we tried to introduce a model to easily interpret the biochemical results. Methods: We retrospectively retrieved records of patients who underwent surgical treatment for uterine masses from 2004 to 2016, and we compared data of 2211 patients with a definitive surgical diagnosis of uterine fibroids and 43 with uterine sarcomas. Quantitative relationships between serum LDH isoenzymes levels, as different single markers or in multiple assays, and the final diagnosis were investigated. Results: LDH isoenzymes levels significantly differed between patients with benign uterine masses or sarcomas. LDH3 isoenzyme exhibited better predictive performances than the other four isoforms. Combining LDH3 with LDH1 isoenzymes into an inverse algebraic relationship, named Uterine mass Magna Graecia (U.M.G.) risk index, the accuracy of markers in discriminating between benign and suspicious malignant uterine masses was significantly enhanced, sensitivity at 100% and specificity at 99.6%, with nine false positive over 2211 benignant cases and no false negative over 43 sarcomas. Conclusions: This retrospective analysis suggests to consider U.M.G. risk index as an inexpensive and accurate prognostic index that, once validated in a prospective study, may help clinicians in discriminating between benignant and suspicious malignant uterine masses.